Raising the bar: genus-specific nested PCR improves detection and lineage identification of avian haemosporidian parasites - Musa, Sandrine; Hemberle, Theo; Bensch, Staffan; Palinauskas, Vaidas; Baltrūnaitė, Laima; Woog, Friederike; Mackenstedt, Ute (Frontiers in Cellular and Infection Microbiology, 2024)
Avian haemosporidian parasites are useful model organisms to study the ecology and evolution of parasite-host interactions due to their global distribution and extensive biodiversity. Detection of these parasites has evolved from microscopic examination to PCR-based methods, with the mitochondrial cytochrome b gene serving as barcoding region. However, standard PCR protocols used for screening and identification purposes have limitations in detecting mixed infections and generating phylogenetically informative data due to short amplicon lengths. To address these issues, we developed a novel genus-specific nested PCR protocol targeting avian haemosporidian parasites. The protocol underwent rigorous testing utilizing a large dataset comprising blood samples from Malagasy birds of three distinct Passeriformes families. Furthermore, validation was done by examining smaller datasets in two other laboratories employing divergent master mixes and different bird species. Comparative analyses were conducted between the outcomes of the novel PCR protocol and those obtained through the widely used standard nested PCR method. The novel protocol enables specific identification of Plasmodium, Haemoproteus (Parahaemoproteus), and Leucocytozoon parasites. The analyses demonstrated comparable sensitivity to the standard nested PCR with notable improvements in detecting mixed infections. In addition, phylogenetic resolution is improved by amplification of longer fragments, leading to a better understanding of the haemosporidian biodiversity and evolution. Overall, the novel protocol represents a valuable addition to avian haemosporidian detection methodologies, facilitating comprehensive studies on parasite ecology, epidemiology, and evolution.